2014
DOI: 10.1016/j.ajpath.2013.10.025
|View full text |Cite
|
Sign up to set email alerts
|

Chemoprevention of Rat Mammary Carcinogenesis by Spirulina

Abstract: Spirulina (SP) (Arthrospira platensis; previously Spirulina platensis) is a filamentous blue-green microalga (cyanobacterium) with potent dietary phytoantioxidant and anticancerous properties. We investigated the chemopreventive effect of SP against 7,12-dimethylbenz[a]anthracene (DMBA)-induced rat breast carcinogenesis, and further studied its underlying mechanisms of action in vitro. Remarkably, SP cleared DMBA-induced rat mammary tumors, which was clearly confirmed by morphological and histological methods.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 21 publications
2
20
0
1
Order By: Relevance
“…Beaten cancer cells are enfeebled and incapable of rejuvenation. Ouhtit et al ( 2014 ) confirmed that an A. platensis treatment of DMBA-induced rat mammary tumor decreased the cancer incidence from 87 to 13%. Immunohistochemical analysis revealed that supplementation with “Spirulina” reduced the expression of Ki-67 and estrogen α.…”
Section: Arthrospira Human Health and Medicine—the Multipmentioning
confidence: 94%
“…Beaten cancer cells are enfeebled and incapable of rejuvenation. Ouhtit et al ( 2014 ) confirmed that an A. platensis treatment of DMBA-induced rat mammary tumor decreased the cancer incidence from 87 to 13%. Immunohistochemical analysis revealed that supplementation with “Spirulina” reduced the expression of Ki-67 and estrogen α.…”
Section: Arthrospira Human Health and Medicine—the Multipmentioning
confidence: 94%
“…Spirulina treatment induced a desquamation of the neoplastic cells leading to eradication of the tumors. A normal epithelial layer formed once the tumor was eradicated [19]. In conclusion, SP exhibited remarkable antitumor activity by inhibiting mammary tumor cell proliferation induced by DMBA in rats.…”
Section: Genestinmentioning
confidence: 87%
“…We have conducted extensive in vitro and in vivo investigations on the effects of C-phycocyanin and spirulina [19]. We utilized MCF7 breast cancer cells for in vitro studies.…”
Section: Genestinmentioning
confidence: 99%
“…Yogianti et al [ 33 ] showed that spirulina exerts antitumor effects against UVB-induced skin tumor development in mice. In addition, it has been reported that spirulina exerts a chemopreventive effect against 7,12-dimethylbenz[a]anthracene-induced breast carcinogenesis [ 34 ] and against dibutyl nitrosamine-induced liver cytotoxicity and carcinogenesis [ 12 ] in rat. The discrepancy between these data and our results might be attributed to differences in the experimental conditions, the model of the solid tumor used, or the limited ability of spirulina to penetrate through Ehrlich solid tumor tissue and to reach all of the tumor cells in a potentially lethal concentration.…”
Section: Discussionmentioning
confidence: 99%